The relationship of teachers' and students' motivation in ELT in Malta: a mixed methods study - Mifsud, Maria (2011)
This thesis investigates the relationship between the motivation of secondary school teachers and students of English in Malta. The study involved 34 Form Four teachers of English and their 612 students (15 year-olds). A mixed methods research methodology, involving a survey and an interview study which complemented each other, was employed. The survey measured levels of teacher and student motivation and the relationship between them through questionnaires. Some of the teachers who had taken part in the survey were then interviewed about their motivation to teach and their perceptions of the relationship between this motivation and their students' motivation to learn. The results show that mainly two factors link the motivation of teachers and students of English. These are a good rapport between teachers and their students and high teacher efficacy. Both of these factors increase the motivation of the students and their teachers. Type of school and the students' attitudes toward Maltese speakers of English were also found to be influencing factors in the relationship between teacher and student motivation. Recommendations which stem from the study are that teachers should seek ways of professional self-improvement through support groups and Continual Professional Development courses. Other suggestions, both at the school level and the policy level, are put forward. These recommendations, if implemented, should improve teacher motivation which would in turn lead to improved student motivation as a positive relationship between the two has been established. The study is one of its kind in that it has established, for the first time, that an empirical link exists between teacher and student motivation.